MENTAL HEALTH FOR STUDENT IN FACING ADAPTING NEW HABITS WITH COUNSELING QUR’AN SURAH AR-RAD VERSE 28 (Al-Tazkiah Jurnal Bimbingan dan Konseling Islam, 2023)
This research aims to describe mental health and the effect of counseling Qur'an Surah Ar-Rad verse 28 on mental health in facing adapting new habits. This research method is a quantitative research with descriptive statistical methods. The research subjects were student who experienced mental health problems in facing adaptating new habits. Data were obtained through a questionnaire on the implementation of counseling Qur’an Surah Ar-Rad verse 28 and Self-Reporting Questionnaire (SRQ) 20. Data analysis used a simple regression coefficient test (t-test). The results showed that the general description of the mental health of students was in the category indicated to have mental health problems by 58.3%, and 41.7% were not indicated to have mental health problems. Meanwhile, the student response to the counseling of the Qur'an in the letter ar-rad verse 28 shows that 67% are very satisfied, 33% are quite satisfied and 0% are very dissatisfied. The results also show that the influence of counseling Qur'an Surah Ar-Rad verse 28 on mental health in facing adapting new habits can be seen with a pv value of 0.000 with a percentage of 58.7%. The practice of counseling Qur'an Surah Ar-Rad verse 28 can be said to be quite effective making mental health in facing adapting new habits